2015
DOI: 10.1371/journal.pone.0133082
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel C-Terminal CIB2 (Calcium and Integrin Binding Protein 2) Mutation Associated with Non-Syndromic Hearing Loss in a Hispanic Family

Abstract: Hearing loss is a complex disorder caused by both genetic and environmental factors. Previously, mutations in CIB2 have been identified as a common cause of genetic hearing loss in Pakistani and Turkish populations. Here we report a novel (c.556C>T; p.(Arg186Trp)) transition mutation in the CIB2 gene identified through whole exome sequencing (WES) in a Caribbean Hispanic family with non-syndromic hearing loss. CIB2 belongs to the family of calcium-and integrin-binding (CIB) proteins. The carboxy-termini of CIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…The profound deafness observed in CIB2 −/− mice, lacking a functional CIB2 protein for all four Cib2 splice isoforms (Fig A, see also Giese et al , ; Zou et al , ), is reminiscent of the prelingual severe‐to‐profound hearing loss observed in DFNB48‐affected patients (Riazuddin et al , ; Patel et al , ; Seco et al , ; and this study). However, none of the cochlear phenotypes associated with the lack of CIB2 described above were observed in CIB2‐defective vestibular organs.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The profound deafness observed in CIB2 −/− mice, lacking a functional CIB2 protein for all four Cib2 splice isoforms (Fig A, see also Giese et al , ; Zou et al , ), is reminiscent of the prelingual severe‐to‐profound hearing loss observed in DFNB48‐affected patients (Riazuddin et al , ; Patel et al , ; Seco et al , ; and this study). However, none of the cochlear phenotypes associated with the lack of CIB2 described above were observed in CIB2‐defective vestibular organs.…”
Section: Discussionsupporting
confidence: 67%
“…These expression studies therefore provided no support for a potential link between CIB2 and Usher syndrome. Finally, following on from the initial identification of CIB2 mutations in Pakistani and Turkish families (Riazuddin et al , ), new CIB2 mutations have been found in Dutch, Caribbean Hispanic (Patel et al , ; Seco et al , ) and Iranian and Palestinian Arab (this study, see Fig A–C) families. Of all the nine mutations of CIB2 described to date (including those described here), only the p.Glu64Asp missense variant, described in one Pakistani family, has been reported to cause USH1J (Riazuddin et al , ).…”
Section: Discussionsupporting
confidence: 56%
“…The deletion was on data from other missense variants in CIB2, which do not have this type of impact. [12][13][14][15] It is unclear whether CIB2 p.Cys115 would affect the interaction with TMC1 or TMC2. 15 The p.Val75Met variant has been previously described 17 ( Figure 1F).…”
Section: Discussionmentioning
confidence: 99%
“…Missense variants in CIB2 also do not affect protein localization. [12][13][14][15] There are also important phenotypic differences. Mouse models of USH caused by MYO7A, USH1C, CDH23, PDCH15 and USH1G (the genes responsible for USH1B, USH1C, USH1D, USH1F and USH1G, respectively, in humans) all share a common phenotype: congenital profound deafness and vestibular dysfunction manifested as a visible head-bobbing and circling phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation